Reassessment of the age and depositional environments of the Eocene Çayraz Formation, a reference unit for Tethyan larger benthic foraminifera (Haymana Basin, central Turkey). (15th May 2020) - Özcan, Ercan; Hakyemez, Aynur; Çiner, Attila; Okay, Aral I.; Soussi, Mohamed; Boukhalfa, Kamel; Osman Yücel, Ali
Highlights: Çayraz Formation show a depositional spectrum ranging from inner to outer-ramp and basin. The lower unit below the pelagic marls of the middle unit shows a shallowing-upward trend. The planktonic foraminifera from the middle unit of the Çayraz Formation indicate P9 Zone. Abstract: The Çayraz Formation, a reference unit for Tethyan Ypresian-middle/late Lutetian larger benthic foraminifera (Haymana Basin, central Turkey), is a thick (>350 m) 'shallow-marine' mixed carbonate-siliciclastic sequence, divided into lower, middle and upper units. The lower and upper units predominantly consist of rhythmic intercalations of limestone and marly/silty beds with abundant larger benthic foraminifera (LBF), and the middle unit is composed of massive fine siliciclastic sediments, mostly barren in LBF and macrofossils. By studying three sections (ÇAYA, ÇAYB, and YEŞ), encompassing the lower unit, we show that the Çayraz Formation (ca. 100 m-thick) displays notable vertical and lateral variability in benthic fauna and facies along an SE-NW transect at its type locality near Çayraz village. The distribution of LBF and facies patterns indicate a general shallowing upward trend, with more open marine environments in the easterly section (ÇAYA) and restricted shallow marine to continental environments with low diversity fauna in the westerly section (YEŞ). A depositional setting ranging from outer to inner-ramp with continental influence only in the westerly section is proposed. Key orthophragminid and alveolinid taxa from the lower unit of the Çayraz Formation indicate shallow benthic zones (SBZ) 9/10 for its lower part, and SBZ 12 for its upper part, suggesting a late Ypresian age. The massive marly/silty section of the middle unit of the Çayraz Formation overlies the Alveolina -bearing limestones in all sections and yielded abundant planktonic foraminifera suggestive of P9 Zone. This implies a sharp environmental transition from platform to basin across the Ypresian-Lutetian boundary.